Educação e saúde: da queixa de professores ao diagnóstico da equipe de saúde no município de Santo André - Pires, Viviane Ferrareto da Silva (2021)
The objective of this study is to analyze the relationship between teacher complaints in reports of diagnostic health evaluations and the content of the reports made by the multidisciplinary clinical team responsible for making the diagnostics. Strictly documentary, the study was conducted in the city of Santo Andre in the state of São Paulo. The information contained in this study came from 474 reports of analyzed students between the years 2012 and 2014 and released by the responsible education organization. The purpose of this thesis was to look at the relationship between different types of school failure, especially low academic performance and the resultant medical diagnosis, with emphasis on students with intellectual disabilities. Vygotsky‟s socio-historical theory on the development of cognitive function in higher education institutions required that the study not only cover students with intellectual disabilities, but also cover all other students. According to Bourdieu‟s studies, in reference to the teacher‟s judgment, the analysis exceeded the restricted level of training of education and health professionals. In addition, the analysis shows that the reports need to be analyzed by official health organizations that relate the school failure with the students biological or psychological conditions. The statistical treatment software, Sphinx iQ2, was used for building simple and cross charts, organizing, reenforcing and analyzing the collected data. The main findings can be summarized as follows: the attribution of disorders in all referred students, as well as the excessive amount of intellectual disability diagnoses showed that medical diagnoses were used to explain the low school performance. IQ, as a determinant of intellectual disability, and the intense utilization of standard methods